Assessment of Patient Satisfaction and Pain Control in Regional Anaesthesia with and Without Sedation During Orthopaedic Procedures - Furqan Akram, Fareed Naeem, Usman Zeeshan³, Gul Sher, Mohammad Baqir Ali Khan, Ali Kashif, Farah Naz Tahir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
A randomized controlled trial evaluated 180 adults undergoing elective distal-limb orthopaedicsurgery under regional anaesthesia (RA) with sedation (n=90) versus RA without sedation (n=90).Primary outcomes were patient satisfaction